Phenol-soluble modulins form amyloids in contact with multiple surface chemistries - Marichal, Laurent; Bagnard, Lucie; Sire, Olivier; Vendrely, Charlotte; Bruckert, Franz; Weidenhaupt, Marianne (Biochimica et biophysica acta. General subjects, 2023)
Functional amyloids are commonly produced by many microorganisms and their biological functions are numerous. Staphylococcus aureus can secrete a group of peptides named phenol-soluble modulins (PSMs) in their biofilm extracellular matrix. PSMs have been found inside biofilms both in their soluble form and assembled into amyloid structures. Yet, the actual biological function of these amyloids has been highly debated. Here, we assessed the ability of PSMs to form amyloids in contact with different abiotic surfaces to unravel a potential unknown bioadhesive and/or biofilm stabilization function. We combined surface plasmon resonance imaging, fluorescence aggregation kinetics, and FTIR spectroscopy in order to evaluate the PSM adsorption as well as amyloid formation properties in the presence of various surface chemistries. Overall, PSMs adsorb even on low-binding surfaces, making them highly adaptable adsorbants in the context of bioadhesion. Moreover, the PSM aggregation potential to form amyloid aggregates is not impacted by the presence of the surface chemistries tested. This versatility regarding adsorption and amyloid formation may imply a possible role of PSMs in biofilm adhesion and/or structure integrity. •Phenol-soluble modulins can adsorb on highly different surface chemistries.•This adsorption versatility makes PSMs potential bioadhesion markers.•The amyloid formation of PSMs seems independent of surface chemistry.•A biological function for amyloid PSMs remains elusive.